Analysis of the Learning Process Block Centers Based on Mutual Cooperation in Forming Children's Character Through the Collaborative Reflection Model in Daycare - Amanda Nur Adliyani; Asep Kurnia Jayadinata; Dhea Ardiyanti (Program Studi Pendidikan Islam Anak Usia Dini, Institut Agama Islam Ma'arif (IAIMNU) Metro Lampung, 2026)
The character of mutual cooperation is one of the values that need to be instilled from an early age through meaningful learning experiences. However, in practice, children are still found to play individually, lack sharing, and are not yet able to work together in group activities. This study aims to analyze the learning activities of the block center based on mutual cooperation through the Collaborative Reflection model and identify factors that support and hinder the formation of mutual cooperation character in children at Jagad Solution Daycare. The study used a qualitative approach with a case study design. Data were obtained through observations during five meetings, interviews with teachers, and documentation, then analyzed by data reduction, data presentation, and drawing conclusions. The results showed that the implementation of learning was carried out through the stages of habituation, Circle time, exploration of playing with blocks, reflection during the activity process, and reflection at the end of the learning. During the study, the character of mutual cooperation developed gradually, marked by an increase in children's ability to share, cooperate, accept friends' opinions, help complete tasks, and comply with play rules. Learning success is supported by the use of block media that encourages social interaction, consistent habituation, and the role of the teacher as a facilitator through trigger questions and reflective discussions. Meanwhile, differences in children's developmental stages, the still limited attention span of the 2-year-old age group, and the need for special assistance for some children are factors that influence the learning process. This study shows that the integration of a mutual cooperation-based block center with Collaborative Reflection has the potential to be an alternative learning strategy that supports the formation of early childhood character through collaborative play experiences and reflection.